Lebanon’s Second Republic - Paul Kingston (International Institute of Islamic Thought, 2004)
It has now been over a decade since Lebanon’s long civil war ended. Indeed, the new constitutional structures that emerged from the war – Lebanon’s second republic – will soon have a longer life than the war itself. This book examines both the depth and sustainability of Lebanon’s new-found stability and brings together both academics specializing in contemporary Lebanese affairs as well as several Lebanese professionals. It is divided into three sections: Lebanon’s future in the context of the Middle East peace process, questions of sectarianism and identity within Lebanon, and selected questions relating to social justice and economic performance in the postwar world. The book is also flanked by an introduction and an epilogue written by Ellis. The volume first examines the regional and global contexts in which Lebanon finds itself. Modern Lebanon has always been vulnerable to external interference in its affairs. Hafeez Malik argues that in the nineteenth century, it was the competition between the great powers that led to ...